Application of Geospatial Multiple Criteria Decision Analysis in Siting Combined Cycle Power Plant in Iran - Siavash, Eghbali (2011)
Establishment of a power plant as a main infrastructure requires comprehensive investigation prior to construction phase. Location of power plant is one of the main issues which should be inspected in advance to guarantee its future optimized operation and minimized losses. This study uses the integration of Geographic Information System (GIS) and Multi Criteria Decision Analysis (MCDA) approach to site a Combined Cycle Power Plant (CCPP). This research was implemented in three successive stages which include a small scale map (1:250,000) and a large scale map (1:25,000) site suitability assessments, and a site selection. In the first stage, a site suitability assessment was performed to determine the high potential area in Sistan and Baluchistan province in Iran for CCPP establishment using small scale map (1:250,000). This stage involves a number of processing steps which include: definition of influential siting criteria, relative classification and constraint zones determination, evaluation criteria prioritization (PWC method) and factor maps integration (WLC method). The final result of this stage showed that around 0.03% of province area possesses the highest potential for CCPP establishment. After imposing constraint map, it was found that the north zone of Chabahar port is the only most potential area which is feasible for CCPP construction. In next stage, based on the highest potential area of 1:250,000 scale analysis, the same steps of site suitability assessment were implemented to obtain the highest potential regions using 1:25,000 scale map. The result illustrates that around 12% of study area had the highest potential for CCPP establishment. Afterward, by imposing final constraint map and CCPP areal limitation, 3 alternatives were designed as final candidate sites for CCPP establishment. In the final stage, a spatial decision making was performed to determine the best site for CCPP placement and the result shows that Site 1 is the best site for its establishment. For evaluating the robustness of final result, a sensitivity analysis was performed based on two criteria weights as the most controversial. The sensitivity analysis results confirmed the persuasive stability of final result against perturbation in criteria weights. The experts’ opinions in all stages agreed on high importance of water and fuel provision in locating the CCPP establishment site. Also the measuring index for the load demand criterion which is the load demand growth in previous studies emerged incomplete and was replaced by the load demand density.